Medication errors in patients with enteral feeding tubes in the intensive care unit - Seyed Mojtaba Sohrevardi; Mohammad Hossein Jarahzadeh; Ehsan Mirzaei; Mahtabalsadat Mirjalili; Arefeh Dehghani Tafti; Behrooz Heydari (Wolters Kluwer Medknow Publications, 2017)
Objective: Most patients admitted to Intensive Care Units (ICU) have problems in using oral medication or ingesting solid forms of drugs. Selecting the most suitable dosage form in such patients is a challenge. The current study was conducted to assess the frequency and types of errors of oral medication administration in patients with enteral feeding tubes or suffering swallowing problems. Methods: A cross-sectional study was performed in the ICU of Shahid Sadoughi Hospital, Yazd, Iran. Patients were assessed for the incidence and types of medication errors occurring in the process of preparation and administration of oral medicines. Findings: Ninety-four patients were involved in this study and 10,250 administrations were observed. Totally, 4753 errors occurred among the studied patients. The most commonly used drugs were pantoprazole tablet, piracetam syrup, and losartan tablet. A total of 128 different types of drugs and nine different oral pharmaceutical preparations were prescribed for the patients. Forty-one (35.34%) out of 116 different solid drugs (except effervescent tablets and powders) could be substituted by liquid or injectable forms. The most common error was the wrong time of administration. Errors of wrong dose preparation and administration accounted for 24.04% and 25.31% of all errors, respectively. Conclusion: In this study, at least three-fourth of the patients experienced medication errors. The occurrence of these errors can greatly impair the quality of the patients' pharmacotherapy, and more attention should be paid to this issue.